Strategies for International Negotiation with Uncooperative Countries: North Korea as a Model: international and political journal - Motlak, Assistant Prof. Dr. Donia Jwad (The International and Political Journal, 2024)
Despite the importance of international cooperation as the other face of international interactions in addition to conflict, and despite its importance in maintaining international peace and security and its inclusion in Article 1 of the United Nations Charter as the second goal of the international organization after maintaining international peace and security, its concept has not received consensus among schools of thought in international relations. While the realist theory, with its various intellectual trends, focused on the role of the state in achieving this cooperation to ensure mutual interests between states, the liberal theory, with its various trends, emphasized the role of international institutions in building this cooperation. Then, the constructivist theory added other variables that can contribute to the success of the state’s attempts in international cooperation strategies, such as identity and the social structure of the state. As long as the interests of states conflict and the components of strength and capacity they possess and the nature of the roles they play in the international system vary, states have different approaches to cooperation with other states and units of the international system in a way that ensures the achievement of these interests. This results in dividing states into states that cooperate with effective international organizations and powers and others that do not cooperate. There are many countries that do not cooperate with international strategies in some issues for various reasons, including the rejection of unilateral hegemony over the international system or the system of alliances that are linked to it or the nature of their roles in the conflict equations that they are based on regionally and internationally, such as North Korea. This imposes on the United Nations, the Security Council and the International Atomic Energy Agency, as the parties concerned with the North Korean nuclear program, to adopt negotiation strategies of a different nature in terms of stages, dialogues and tactics, due to the threat this program poses to the international balances that underlie the security and stability of East Asia and the international system in general. This paper examines the concept of international cooperation, as well as defining negotiation strategies from a theoretical perspective and examining the international negotiation strategies adopted by the International Atomic Energy Agency, the Security Council, the United States of America, the Russian Federation and China with North Korea regarding its nuclear program.